Do medical students with a disability experience adverse educational outcomes on UK medical courses?. (3rd April 2023) - Revell, Kirsten; Nolan, Helen
Abstract: Background: International data demonstrate that medical students with disabilities experience differential awarding. One cross-sectional study finds lower graduation rates and scores in written exams, with no impact on clinical exams. Disabled students graduated with lower decile scores. This quantitative, retrospective, longitudinal study explored the impact of disability on exam performance, course performance and course discontinuation. Method: Anonymised data were obtained for 1743 students on a UK graduate medical programme from 2011 to present. Statistical tests, including t -tests and one-way ANOVA were conducted for main effects of demographic variables on exam results and categorical outcomes. Regression models established the effects of variables and sub-categories of variables on results and categorical outcomes. Results: Significant main effects of disability on exam scores were identified, as well as failure probability. Regressions showed significant differences in outcomes between different types of disability, with mental health conditions predicting course discontinuation. A significant amplifying effect was found for BAME students with disability. Conclusion: Disability had a significant negative impact on all course outcomes, illustrating inequity in medical training and an area of focus for curriculum development. Intersectional data identified a key disadvantaged subgroup of medical students.